2002
DOI: 10.1073/pnas.222519799
|View full text |Cite
|
Sign up to set email alerts
|

Conformational energetics of stable and metastable states formed by DNA triplet repeat oligonucleotides: Implications for triplet expansion diseases

Abstract: We have embedded the hexameric triplet repeats (CAG)6 and (CTG) 6 between two (GC)3 domains to produce two 30-mer hairpins with the sequences d[(GC) 3(CAG)6(GC)3] and d[(GC)3(CTG)6(GC)3]. This construct reduces the conformational space available to these repetitive DNA sequences. We find that the (CAG) 6 and (CTG)6 repeats form stable, ordered, single-stranded structures. These structures are stabilized at 62°C by an average enthalpy per base of 1.38 kcal⅐mol ؊1 for the CAG triplet and 2.87 kcal⅐mol ؊1 for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 68 publications
7
58
2
Order By: Relevance
“…Breslauer and co-workers (34) report that, once formed, a sufficiently long single stranded hairpin state is stable under physiological conditions and requires thermal disruption for it to revert to duplex DNA, despite the higher stability of the latter state. Thus, once formed, the hairpin flap intermediate may not equilibrate readily to other intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…Breslauer and co-workers (34) report that, once formed, a sufficiently long single stranded hairpin state is stable under physiological conditions and requires thermal disruption for it to revert to duplex DNA, despite the higher stability of the latter state. Thus, once formed, the hairpin flap intermediate may not equilibrate readily to other intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…Völker et al (17,19) also reported an irreversible conversion to duplex by ⍀-DNA structures that contain a (CAG) 6 or (CTG) 6 single-stranded hairpin embedded within duplex. Because the hairpin to duplex conversion process is irreversible, we conclude that the FL-(CAG) 10 -DCL/ (CTG) 10 duplex is the thermodynamically more stable state at low temperature.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 In all three cases very strong binding was found, see Table 1, with binding constants in the range K = 1.7 × 10 7 (± 0.5) M strongly suggests that quenching of emission is due to electron transfer from the DNA bases to the diquat centre. 42 The efficiency of this process is improved when the oxidizing agent is held in close proximity to the bases. Hence the extent of quenching can be taken as a further indication of tight binding.…”
Section: Investigation Of Dna Binding With 1-4 Absorption Titrationsmentioning
confidence: 99%